2020
DOI: 10.1101/2020.11.06.370957
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Badger territoriality maintained despite disturbance of major road construction

Abstract: Road ecology has traditionally focused on the impact of in-situ and functional roads on wildlife. However, road construction also poses a major, yet understudied, threat and any implications for key aspects of animal behaviour are unknown. There are concerns that environmental disturbances, including major roadworks, can disrupt badger (Meles meles) territoriality, promoting the spread of tuberculosis to cattle. To address these knowledge gaps, the ranging behaviour of a medium-density Irish badger population … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
1
1
0
Order By: Relevance
“…We find average recapture distances of 671 m; this is comparable to the nightly distance moved (651 m) assessed by trapping in another Irish badger population, which inhabits a very similar, agriculture‐dominated landscape (Gaughran et al., 2021).…”
Section: Discussionsupporting
confidence: 75%
“…We find average recapture distances of 671 m; this is comparable to the nightly distance moved (651 m) assessed by trapping in another Irish badger population, which inhabits a very similar, agriculture‐dominated landscape (Gaughran et al., 2021).…”
Section: Discussionsupporting
confidence: 75%
“…Interestingly, while disruptions to wildlife host populations (i.e. badgers) social behaviour were believed to be the cause (Barroso et al, 2022), concurrent research found no changes to wildlife territoriality while subjected to disturbances via road construction (Gaughran et al, 2021). This clearly highlights our poor understanding of the mechanism behind fluctuations in disease risk in disturbed landscapes.…”
Section: Introductionmentioning
confidence: 99%